' … vayan a San Miguel de Allende, además lleven su visa y su diccionario los que no sepan hablar inglés pues ya se han apropiado de todo los gringos.' The discursive struggle for interculturality in a gentrified hybrid Mexican city. (2nd January 2023) - Anderson, Christopher; Delgado, Ireri Armenta
ABSTRACT: This paper focuses on interculturality in the discursive construction of the Mexican city of San Miguel de Allende that is culturally hybrid due to Americanisation and gentrification caused by North American migration and tourism. Constructing their own community as 'expats', this homogenous group produces and reproduces a dominant discourse that normalises Americanisation and gentrification. There is, however, a resistant discourse from multiple voices, both North American and Mexican, that problematises this hybridity in terms of negative consequences for local Mexicans of rising costs, displacement, and a sense of alienation, particularly felt in how English has become a lingua franca .